The Preconditions of Parallel Education in Lithuanian Schools in 1918-1940 - Pečkus, Kęstutis (Acta Paedagogica Vilnensia, 1993)
Education system of a school consists of two units – learning activities compulsory to all students and their activities after school, during homework. The latter is usually called “extra-curricular”, “after school” activities. However, these concepts define education as a closed process that takes place at school or within its environment, denying its inclusive meaning. An inclusive school’s value to describe the interaction between school and life to discuss is best expressed by the concept of “parallel development”. While this term has not been used in the time the article discusses, .i.e. the period of 1918-1940, but it is most suitable to reveal the essence of integrating education, which much has been widely reflected by S. Šalkauskis, A. Maceina, A. Šerkšnas, A. Busilas and others. The article presents historical overview of the problem of parallel education, focusing on human nature, individuality and uniqueness of fostering the free human development, schools and society, the individual and the community. It also analyzes how the theory of pedagogy, pedagogical currents would find resonance in independent Lithuania considering the school’s mission, in the debates on its relationship with culture, society, political ideologies, etc.